Determination of Entrepreneurial Education and Attitudes, Subjective Norms, and Entrepreneurial Intentions Towards Ecopreneur Behavior of Culinary Entrepreneurs in the Special Region of Yogyakarta - Riani, Lilia Pacsa; Mulyani, Endang; Manik, Yuni Mariani; Supriyanto, Supriyanto; Sumarsih, Sri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the effects of entrepreneurship learning, entrepreneurial attitudes, subjective norms, and entrepreneurial intentions on ecopreneurial behavior. Guided by the Theory of Planned Behavior (Ajzen, 1991), the research employed a quantitative approach using path analysis to examine direct and indirect relationships among the variables. This study examines how entrepreneurship learning influences ecopreneurial behavior through attitudes, subjective norms, and entrepreneurial intention. Primary data were collected through questionnaires from culinary MSME entrepreneurs in the Special Region of Yogyakarta. The research population comprised active culinary entrepreneurs, with samples selected using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with AMOS to test direct and indirect relationships among variables and validate the proposed behavioral model. The findings show that entrepreneurship learning significantly enhances entrepreneurial attitudes and intentions, with intention mediating the relationship between learning and ecopreneurial behavior. Experiential learning, mentoring, and formal education emerge as key drivers of sustainable entrepreneurial intention. Overall, effective entrepreneurship learning strengthens ecopreneurial behavior, supporting sustainable economic development among culinary entrepreneurs.